Liquid crystal polymer film based on covalent organic framework photo-thermal agent as well as preparation method and application of liquid crystal polymer film
By introducing covalent organic framework (COF) photothermal agent into the liquid crystal polymer film, the problems of poor stability and single function of photothermal agent in existing photothermal actuators are solved, and a photothermal-responsive liquid crystal polymer film with high stability and versatility are achieved.
Patent Information
- Application Number
- CN202411545464.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-01
AI Technical Summary
Existing photothermal actuators face problems such as poor stability of photothermal agents, easy photobleaching, and single function.
A liquid crystal polymer film based on a covalent organic framework (COF) photothermal agent is used to form a hybrid-oriented COF-liquid crystal polymer film by preparing COF powder, nanoparticles and heating with the liquid crystal mixture.
The thermal stability and light stability of the photothermal agent are improved, the dispersion and functionality are enhanced, and the reversible curling and bending movement of the liquid crystal polymer matrix is realized under near-infrared light or volatile solvent vapor stimulation.
Smart Images

Figure CN119529182A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the fields of COF materials and liquid crystal materials, and in particular to a covalent organic skeleton-based photothermal agent liquid crystal polymer film and a preparation method and application thereof. Background Art
[0002] Covalent organic frameworks (COFs) have been at the forefront of nanomaterial research in the past decade due to their high porosity, high specific surface area, high stability, and controllable chemical structure. They are a rapidly developing class of nanomaterials, mainly used in batteries, supercapacitors, catalysis, sewage treatment, sensors, drug delivery, and gas separation. However, COFs are hindered from further development due to their insolubility and poor processability. Therefore, mixing COFs with liquid crystal matrices is a good solution to these problems, and liquid crystal polymers have good processability and can retain the unique properties of COFs and liquid crystal polymers in a mixture based on two different components. COFs have the following advantages as photothermal agents: good photostability, adjustable light absorption range, and functionalized directional design to achieve multiple functions. COFs can have a conjugated structure through structural design, which can significantly improve photothermal absorption and photostability, making them have high photothermal conversion capabilities under near-infrared light irradiation.
[0003] Photothermal responsive liquid crystal polymers usually require the addition of photothermal agents to the liquid crystal polymer matrix, and common photothermal agents include small molecule dyes, graphene, carbon nanotubes, metal particles, conjugated polymers, etc. Among them, traditional photothermal dyes usually experience photobleaching, which reduces the photothermal conversion efficiency; the compatibility of metal particles with the liquid crystal polymer matrix is relatively poor; graphene and carbon nanotubes have poor dispersion in liquid crystal polymers and are not easy to further functionalize. COF has a flexible structure and can be used to design the organic skeleton according to the use requirements, so the covalent organic skeleton can be designed according to the needs of the photothermal agent. The preparation method of the present invention is simple, the materials are easily available, the reaction is mild, and it is convenient for industrial-scale production. Summary of the invention
[0004] Based on this, the present invention provides a covalent organic skeleton-based photothermal agent liquid crystal polymer film to solve the problems faced by existing photothermal-driven actuators, such as poor stability of the photothermal agent, easy photobleaching, and single function.
[0005] To achieve the above object, on the one hand, the present invention provides a covalent organic skeleton-based photothermal agent liquid crystal polymer film, which comprises the following steps:
[0006] S1. Using tetrakis(4-aminophenyl)porphyrin and aldehyde monomer as raw materials, COF powder is prepared, wherein the aldehyde monomer is selected from at least one of formulas (1) to (3):
[0007]
[0008] In formula (1), the value of a is an integer between 6 and 18;
[0009] S2, adding COF powder and aniline to tetrahydrofuran, placing in an ultrasonic crusher for ultrasonic crushing, washing, and drying to obtain COF nanoparticles;
[0010] S3, 8-12 mg COF nanoparticles and 150 mg liquid crystal mixture are mixed and heated at 60-100° C. to obtain a uniformly mixed precursor solution, wherein the liquid crystal mixture is composed of the following raw materials:
[0011] 4-methoxyphenyl 4-((6-(acryloyloxy)hexyl)oxy)benzoic acid methyl ester 45-50wt%;
[0012] 15-20 wt% of 4-cyanophenyl 4-((6-(acryloyloxy)hexyl)oxy)benzoic acid methyl ester;
[0013] 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene 30-35wt%;
[0014] Initiator benzoin diethyl ether 0.5-1wt%;
[0015] S4. Pour the precursor liquid into a hybrid oriented liquid crystal box and polymerize it under ultraviolet light to obtain a hybrid oriented COF-liquid crystal polymer film.
[0016] As a further preferred technical solution of the present invention, step S1 specifically prepares COF powder according to the following method:
[0017] Tetrakis(4-aminophenyl)porphyrin and aldehyde monomer are added to a reaction container in a molar ratio of 1:2, and a reaction solvent and a catalyst are added, and ultrasonic mixing is performed. The reaction container is then subjected to freeze-pump-thaw degassing cycles at 77K for multiple times, and then the reaction container is sealed under vacuum, and after it is heated to room temperature, it is placed in an oil bath at 100-120°C. After the reaction is completed, it is washed and vacuum dried to finally obtain a dark brown COF powder; wherein the reaction solvent is 0.5ml-1ml of ethanol and 0.5ml-1ml of o-dichlorobenzene, and the catalyst is 0.05ml-0.2ml of a 6M acetic acid aqueous solution.
[0018] As a further preferred technical solution of the present invention, in step S3, the COF nanoparticles and the liquid crystal mixture are vortexed and mixed in a vortex machine.
[0019] As a further preferred technical solution of the present invention, in step S3, after the COF nanoparticles and the liquid crystal mixture are uniformly mixed, they are heated at 70-90°C and kept warm for 12-24 hours, and the further preferred heating temperature is 80°C.
[0020] As a further preferred technical solution of the present invention, in step S3, 12 mg of COF nanoparticles are mixed with 150 mg of a liquid crystal mixture, wherein the liquid crystal mixture is composed of the following raw materials:
[0021] 4-methoxyphenyl 4-((6-(acryloyloxy)hexyl)oxy)benzoic acid methyl ester 49.8wt%;
[0022] 4-cyanophenyl 4-((6-(acryloyloxy)hexyl)oxy)benzoic acid methyl ester 16.6wt%;
[0023] 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene 33.1wt%;
[0024] Initiator: benzoin diethyl ether 0.5wt%.
[0025] As a further preferred technical solution of the present invention, in step S4, a hybrid-oriented liquid crystal cell with an inner cavity width of 50-100 microns is used, and more preferably, the inner cavity width is 80 microns.
[0026] As a further preferred technical solution of the present invention, in step S4, after the precursor solution is poured into the liquid crystal box, it is kept at 45°C for 5-15 minutes and heated at 5mW / cm 2 Polymerize under 365 nm UV light for 20-30 seconds.
[0027] According to another aspect of the present invention, the present invention also provides a liquid crystal polymer film, which is prepared by the above method.
[0028] According to another aspect of the present invention, the present invention also provides an application of a liquid crystal polymer film as an actuator, wherein the actuator comprises at least one piece of the liquid crystal polymer film, and when the liquid crystal polymer film is stimulated, a phase change occurs, and its vertical orientation surface expands and its parallel orientation surface contracts, so that the actuator undergoes reversible bending or torsional deformation; the stimulation is near-infrared light stimulation, or solvent vapor stimulation of at least one of dichloromethane, toluene, tetrahydrofuran, and acetone. The actuator can be used in a mechanical actuator or a brake for multi-degree-of-freedom motion.
[0029] Compared with the prior art, the present invention can achieve the following beneficial effects:
[0030] The present invention adds COF nanoparticles as photothermal agents in the liquid crystal matrix, which has the advantages of good thermal stability and good light stability compared with traditional photothermal agents; in addition, compared with the metal particle photothermal agent, the dispersibility is better, and no surface treatment is required to improve the dispersibility; compared with CNT and GO photothermal agents, COF can usually meet the experimental needs through directional design, and no acrylate grafting is required again. COF-liquid crystal polymer film can actuate the liquid crystal polymer matrix to reversibly curl and bend under volatile solvent vapor or near-infrared light conditions, so it has good application prospects in the fields of mechanical actuator robots, near-infrared light sensors, solvent vapor sensors, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0032] Figure 1 The structural formulas of liquid crystal monomers HCM 021, HCM 020, C6M and initiator Irgacure 651 are shown in FIG.
[0033] Figure 2 The POR-BHA COF synthesis scheme of Example 1 is shown.
[0034] Figure 3 The PXRD pattern of POR-BHACOF of Example 1 is shown.
[0035] Figure 4 The SEM image of the POR-BHA COF-liquid crystal polymer film of Example 1 is shown, with the upper surface of the hybrid oriented composite film on the left, the lower surface of the hybrid oriented composite film in the middle, and the upper surface of the hybrid oriented composite film on the right and the cross-section of the hybrid oriented composite film in the middle.
[0036] Figure 5 The SEM image of the pure liquid crystal polymer film of Comparative Example 1 is shown, the left side is the upper surface of the hybrid oriented liquid crystal polymer film, the middle is the lower surface of the hybrid oriented liquid crystal polymer film, and the right side is the cross section of the hybrid oriented liquid crystal polymer film.
[0037] Figure 6 A POM image in transmission mode of the POR-BHA COF-liquid crystal polymer film of Example 1 is shown.
[0038] Figure 7 A POM image in transmission mode of the pure liquid crystal polymer film of Comparative Example 1 is shown.
[0039] Figure 8The temperature of the POR-BHA COF-LCP actuator of Example 1 is plotted as a function of 808nm lamp irradiation time, wherein the lower figure corresponds to the upper figure, mainly reflecting that the actuator rapidly heats up under light irradiation, resulting in response behavior.
[0040] Fig. 9 The figure shows the actuation process of the POR-BHA COF-liquid crystal polymer actuator of Example 1 under DCM solvent vapor at room temperature.
[0041] Fig.10 The actual image of the POR-BHACOF-liquid crystal polymer film of Example 1 is shown, with the left side showing the initial state of the material and the right side showing the state under 365 nm light.
[0042] The purpose, features and advantages of the present invention will be further described with reference to the accompanying drawings in conjunction with the embodiments. DETAILED DESCRIPTION
[0043] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0044] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.
[0045] Embodiment 1:
[0046] Raw materials: tetrakis(4-aminophenyl)porphyrin (POR), 2,5-bis((2-hexyldecyl)oxy)terephthalaldehyde (BHA), 4-methoxyphenyl 4-((6-(acryloyloxy)hexyl)oxy)benzoic acid methyl ester (HCM 021), 4-cyanophenyl 4-((6-(acryloyloxy)hexyl)oxy)benzoic acid methyl ester (HCM 020), 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene (C6M), initiator benzoin diethyl ether (Irgacure 651). The liquid crystal monomers HCM 021, HCM020, C6M, and the initiator Irgacure 651 have the following structural formulas: Figure 1 shown.
[0047] According to the above raw materials, the preparation process of the covalent organic skeleton photothermal agent liquid crystal polymer film proposed in this embodiment is as follows:
[0048] Step (1), POR-BHACOF powder synthesis:
[0049] 0.4mmol of tetrakis(4-aminophenyl)porphyrin (POR) and 0.8mmol of 2,5-bis((2-hexyldecyl)oxy)terephthalaldehyde (BHA) were added to a 10ml solvent storage bottle (15mm×80mm), and 1.0ml of ethanol, 1.0ml of o-dichlorobenzene, and 0.1ml of 6M acetic acid aqueous solution were added, and then placed in an ultrasonic cleaner for 10 minutes to mix the mixture evenly, and then rapidly frozen at 77K, and degassed under freeze-pump-thaw for three cycles, and then the bottle stopper was tightened under vacuum, and after the temperature was raised to room temperature, it was reacted in a 120℃ oil bath for three days; after the reaction, the product was washed with N,N-dimethylformamide, tetrahydrofuran, and acetone and placed in a vacuum oven at 120℃ for 24 hours to finally obtain a dark brown COF powder. Its synthesis route can be found in Figure 2 shown. Figure 3 The PXRD pattern of the POR-BHA COF of this example is shown.
[0050] Step (2), preparation of POR-BHACOF nanoparticles:
[0051] In order to make POR-BHACOF disperse well in the liquid crystal polymer matrix, POR-BHACOF was broken by molecular exchange etching. 40.0 mg of COF powder was added to 40 ml of tetrahydrofuran and 112 μL of aniline and ultrasonicated in a 650W ultrasonic crusher for 1 hour. After the ultrasonication, it was washed and dried to obtain COF nanoparticles.
[0052] Step (3), preparation of POR-BHACOF-polymer precursor solution:
[0053] A total of 150 mg of three liquid crystal monomers, 49.8 wt% HCM 021, 16.6 wt% HCM 020, 33.1 wt% C6M, and 0.5 wt% Irgacure 651, were added to 12 mg POR-BHACOF nanoparticles, and the mixture was mixed by vortexing and heated at 80° C. for 24 hours to obtain a uniformly mixed precursor solution.
[0054] Step (4), preparation of POR-BHACOF-polymer film:
[0055] The precursor solution was poured into a 80 μm hybrid oriented liquid crystal cell and kept at 45°C for 15 minutes and at 5 mW / cm 2 The film was polymerized under 365 nm ultraviolet light for 30 seconds to obtain a POR-BHACOF-liquid crystal polymer hybrid alignment film.
[0056] Comparative Example 1:
[0057] As a control experiment of Example 1, a pure liquid crystal polymer film was synthesized, and the specific operation was as follows:
[0058] A total of 150 mg of three liquid crystal monomers, 49.8 wt% HCM 021, 16.6 wt% HCM 020, 33.1 wt% C6M, and 0.5 wt% Irgacure 651, were mixed by vortexing, heated, and kept at 80°C for 24 hours to obtain a uniformly mixed precursor solution; the precursor solution was then poured into an 80 μm hybrid oriented liquid crystal cell, kept at 45°C for 15 minutes, and heated at 5 mW / cm 2 The film was polymerized under 365 nm ultraviolet light for 30 seconds to obtain a pure liquid crystal polymer hybrid alignment film.
[0059] Figure 4 The SEM image of the POR-BHACOF-liquid crystal polymer film of this embodiment is shown. Among them, a, b, and c correspond to the vertical orientation plane, parallel orientation plane, and film cross-sectional view of the POR-BHA COF-liquid crystal polymer film, respectively. By comparing a and b, it is proved that the POR-BHA COF-liquid crystal polymer film presents a Janus structure and therefore has solvent vapor responsiveness. Figure c proves that the POR-BHA COF-liquid crystal polymer film has a hybrid orientation.
[0060] Figure 5 The SEM image of the pure liquid crystal polymer film of Comparative Example 1 is shown. A, b, and c correspond to the vertical orientation plane, parallel orientation plane, and film cross-sectional view of the liquid crystal polymer film, respectively. The comparison between a and b proves that the liquid crystal polymer film presents a Janus structure and therefore has solvent vapor responsiveness; c proves that the liquid crystal polymer film has a hybrid orientation. Figure 4 and Figure 5 Compared with Figure a in Figure 2, it can be seen that the addition of POR-BHA COF makes the vertical orientation surface rougher, while Figure 4 and Figure 5 Compared with Figure c in Figure 3, it is proved that the addition of POR-BHA COF particles affects the orientation of liquid crystals to a certain extent.
[0061] Figure 6 The POM image of the POR-BHACOF-LCP film of this embodiment in the transmission mode is shown; the POM proves that the POR-BHACOF-LCP film has a certain orientation.
[0062] Figure 7 The POM image of the pure liquid crystal polymer film in the transmission mode of Comparative Example 1 is shown, and the POM image proves that the liquid crystal polymer film has good orientation. Figure 6 It can be seen from the comparison that the introduction of COF reduces the degree of orientation to a certain extent. The difference can be clearly seen from the cross-sectional SEM image. Compared with the pure liquid crystal polymer film, it can be seen that the POM of the POR-BHA COF-liquid crystal polymer film has a difference in light and dark changes.
[0063] In summary, pure liquid crystal polymer film is only responsive to solvent vapor, and because of the low roughness of the vertical orientation surface, it will result in a slow response speed and no photothermal response.
[0064] In order to further demonstrate the beneficial effects of the present invention, the strips of the POR-BHACOF-LCP hybrid alignment film of Example 1 (also known as LCP actuators) were subjected to light stimulation and solvent vapor stimulation, respectively, as follows:
[0065] Figure 8 The graph of the temperature of the POR-BHACOF-LCP actuator of this embodiment as a function of the 808nm lamp irradiation time is shown; a strip of 3 cm long and 0.5 cm wide was cut from the POR-BHACOF-LCP film along the perfusion direction perpendicular to the liquid crystal cell and placed under 808nm near-infrared light (light intensity of 625mW / cm 2 ), the actuator bends rapidly within 5 s, and then gradually returns to its initial state after the light source is turned off.
[0066] Fig. 9 The actual diagram of the actuation process of the POR-BHA COF-liquid crystal polymer actuator of this embodiment is shown; the POR-BHA COF-liquid crystal polymer film is cut into strips of 4 cm in length and 0.5 cm in width along the perfusion direction parallel to the liquid crystal box, 20 ml of dichloromethane is added to a 50 ml beaker, and when the actuator is placed above the solvent liquid surface, the actuator bends rapidly within 4 seconds, and when the stimulating gas is removed, the actuator gradually returns to the initial state (the same response behavior is observed when dichloromethane is replaced by tetrahydrofuran, acetone or toluene solvent vapor).
[0067] Fig.10 The actual picture of the POR-BHA COF-liquid crystal polymer film of this embodiment is shown. The POR-BHACOF-liquid crystal polymer film appears dark brown under natural light, and the film exhibits rose red fluorescence under 365nm ultraviolet light; while the pure liquid crystal polymer film is nearly transparent under natural light and has no fluorescent color under 365nm light.
[0068] In order to further demonstrate the beneficial effects of the present invention, based on the preparation method of Example 2, only 2,5-bis((2-hexyldecyl)oxy)terephthalaldehyde (BHA) was replaced with 2,5-bis((2-octylundecyl)oxy)terephthalaldehyde in equal amounts. Finally, a hybrid oriented COF-liquid crystal polymer film was obtained. The actuator formed by the COF-liquid crystal polymer film strip was subjected to light stimulation and solvent vapor stimulation, respectively, and the effect was equivalent to that of Example 1, and the response speed was close.
[0069] Embodiment 2:
[0070] Raw materials: tetrakis(4-aminophenyl)porphyrin (POR), 2,5-bis(octyloxy)terephthalaldehyde (C 6 )、4-methoxyphenyl 4-((6-(acryloyloxy)hexyl)oxy)benzoic acid methyl ester (HCM 021), 4-cyanophenyl 4-((6-(acryloyloxy)hexyl)oxy)benzoic acid methyl ester (HCM 020), 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene (C6M), photoinitiator (Irgacure 651).
[0071] According to the above raw materials, the preparation process of the covalent organic skeleton photothermal agent liquid crystal polymer film proposed in this embodiment is as follows:
[0072] Step (1), POR-C 6 COF powder synthesis:
[0073] Tetrakis(4-aminophenyl)porphyrin (POR) 0.4mmol, 2,5-bis(octyloxy)terephthalaldehyde (C 6 )0.8mmol was added into a 10ml solvent storage bottle (15mm×80mm), and 1.0ml of ethanol, 1.0ml of o-dichlorobenzene and 0.1ml of 6M acetic acid aqueous solution were added, and then placed in an ultrasonic cleaner for 10 minutes to mix the mixture evenly, and then quickly frozen at 77K, degassed under freeze-pump-thaw for three cycles, and then the bottle stopper was tightened under vacuum, and after the temperature was raised to room temperature, it was reacted in a 120℃ oil bath for three days; after the reaction was completed, the product was washed with N,N-dimethylformamide, tetrahydrofuran and acetone and placed in a vacuum oven at 120℃ to dry for 24 hours to finally obtain a dark brown COF powder.
[0074] Step (2), POR-C 6 COF nanoparticle preparation:
[0075] In order to make POR-C 6 COF is well dispersed in the liquid crystal polymer matrix, and POR-C 6 COF was crushed. 40.0 mg of COF powder was added to 40 ml of tetrahydrofuran and 112 μL of aniline, and ultrasonicated in a 650 W ultrasonic crusher for 1 hour. After the ultrasonication, the particles were washed and dried to obtain COF nanoparticles.
[0076] Step (3), POR-C 6 COF-polymer precursor preparation:
[0077] Three liquid crystal monomers (49.8 wt% HCM 021, 16.6 wt% HCM 020, 33.1 wt% C6M) and 0.5 wt% initiator Irgacure 651 were added to POR-C 6 12 mg of COF particles were mixed by vortexing, heated and kept at 80° C. for 24 hours to obtain a uniformly mixed precursor solution.
[0078] Step (4), POR-C 6 COF-liquid crystal polymer film preparation:
[0079] The precursor solution was poured into a 80 μm hybrid oriented liquid crystal cell and kept at 45 °C for 15 minutes and at 5 mW / cm 2 The POR-C 6 COF-liquid crystal polymer hybrid oriented film.
[0080] In order to further demonstrate the beneficial effects of the present invention, the POR-C with hybrid orientation of Example 2 was 6 COF-liquid crystal polymer film strips (actuators) were stimulated by light and solvent vapor, respectively, POR-C 6 The COF-LCP film was cut into strips of 3 cm in length and 0.5 cm in width along the perfusion direction perpendicular to the liquid crystal cell and illuminated under an 808 nm lamp (with a light intensity of 625 mW / cm 2 ) and returns to its initial state after the light source is turned off. 6 The COF-LCP film was cut into strips of 4 cm in length and 0.5 cm in width along the perfusion direction parallel to the liquid crystal box. 20 ml of tetrahydrofuran, acetone, toluene, and dichloromethane were added to 50 ml beakers respectively. When the actuator was placed above the solvent liquid surface, the actuator bent rapidly. After the stimulating gas was removed, the actuator gradually returned to its initial state.
[0081] In order to further demonstrate the beneficial effects of the present invention, based on the preparation method of Example 2, only 2,5-bis(octyloxy)terephthalaldehyde (C 6 ) is replaced by The compound (C 18 ), and finally the hybrid oriented POR-C 18 COF-liquid crystal polymer film. 18 The actuator formed by COF-liquid crystal polymer film strips was subjected to light stimulation and solvent vapor stimulation respectively, and its effect was slightly worse than that of Example 2. The introduction of different carbon chains is mainly for the fluorescence effect, but the influence of carbon chain length on light response and solvent vapor response mainly lies in dispersibility. 6 Than C18 The dispersion is good. The longer the carbon chain is, the more the dispersion is affected, which in turn affects the light response behavior. Specifically, the uneven heating causes slightly different response behaviors, but it can still meet the requirements of the present invention.
[0082] Although specific embodiments of the present invention are described above, those skilled in the art should understand that these are merely examples and that various changes or modifications may be made to the embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is limited only by the appended claims.
Claims
1. A method for preparing a covalent organic framework photothermal agent liquid crystal polymer film, characterized in that: The following steps are involved: S1. Using tetrakis(4-aminophenyl)porphyrin and aldehyde monomer as raw materials, COF powder is prepared, wherein the aldehyde monomer is selected from at least one of formulas (1) to (3): In formula (1), the value of a is an integer between 6 and 18; S2, adding COF powder and aniline to tetrahydrofuran, placing in an ultrasonic crusher for ultrasonic crushing, washing, and drying to obtain COF nanoparticles; S3, 8-12 mg COF nanoparticles and 150 mg liquid crystal mixture are mixed and heated at 60-100° C. to obtain a uniformly mixed precursor solution, wherein the liquid crystal mixture is composed of the following raw materials: 4-methoxyphenyl 4-((6-(acryloyloxy)hexyl)oxy)benzoic acid methyl ester 45-50wt%; 15-20 wt% of 4-cyanophenyl 4-((6-(acryloyloxy)hexyl)oxy)benzoic acid methyl ester; 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene 30-35wt%; Initiator benzoin diethyl ether 0.5-1wt%; S4. Pour the precursor liquid into a hybrid oriented liquid crystal box and polymerize it under ultraviolet light to obtain a hybrid oriented COF-liquid crystal polymer film.
2. The method for preparing a covalent organic framework photothermal agent liquid crystal polymer film according to claim 1, characterized in that: Step S1 specifically prepares COF powder according to the following method: Tetrakis(4-aminophenyl)porphyrin and aldehyde monomer are added to a reaction container in a molar ratio of 1:2, and a reaction solvent and a catalyst are added, and ultrasonic mixing is performed. The reaction container is then subjected to multiple freeze-pump-thaw degassing cycles at 77K, and then the reaction container is sealed under vacuum. After it is heated to room temperature, it is placed in an oil bath at 100-120°C. After the reaction is completed, it is washed and vacuum dried to finally obtain a dark brown COF powder; wherein the reaction solvent is 0.5-1 ml of ethanol and 0.5-1 ml of o-dichlorobenzene, and the catalyst is 0.05-0.2 ml of a 6M acetic acid aqueous solution.
3. The method for preparing a covalent organic framework photothermal agent liquid crystal polymer film according to claim 1, characterized in that: In step S3, the COF nanoparticles and the liquid crystal mixture are mixed by vortexing.
4. The method for preparing a covalent organic framework photothermal agent liquid crystal polymer film according to claim 1, characterized in that: In step S3, after the COF nanoparticles and the liquid crystal mixture are mixed, they are heated at 70-90° C. and kept warm for 12-24 hours.
5. The method for preparing a covalent organic framework-based photothermal agent liquid crystal polymer film according to claim 1, characterized in that: In step S3, 12 mg of COF nanoparticles and 150 mg of a liquid crystal mixture are mixed, wherein the liquid crystal mixture is composed of the following raw materials: 4-methoxyphenyl 4-((6-(acryloyloxy)hexyl)oxy)benzoic acid methyl ester 49.8wt%; 4-cyanophenyl 4-((6-(acryloyloxy)hexyl)oxy)benzoic acid methyl ester 16.6wt%; 1,4-bis-[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene 33.1wt%; Initiator: benzoin diethyl ether 0.5wt%.
6. The method for preparing a covalent organic framework photothermal agent liquid crystal polymer film according to claim 1, characterized in that: In step S4, a hybrid-oriented liquid crystal cell with an inner cavity width of 50-100 microns is used.
7. The method for preparing a covalent organic framework photothermal agent liquid crystal polymer film according to claim 1, characterized in that: In step S4, after the precursor solution is poured into the liquid crystal cell, it is kept at 45°C for 5-15 minutes and heated at 5 m W / cm 2 Polymerize under 365 nm UV light for 20-30 seconds.
8. A liquid crystal polymer film, characterized in that: The method is prepared by any one of claims 1 to 7.
9. Use of the liquid crystal polymer film according to claim 8 as an actuator, characterized in that: The actuator comprises at least one piece of the liquid crystal polymer film, and when the liquid crystal polymer film undergoes a phase change when stimulated, its vertical orientation surface expands and its parallel orientation surface contracts, so that the actuator undergoes reversible bending or torsional deformation; The stimulation is near-infrared light stimulation, or solvent vapor stimulation of at least one of dichloromethane, toluene, tetrahydrofuran, and acetone.
Citation Information
Patent Citations
COFs film material with ultra-low dielectric constant
CN109293957A
Responsive porous ionic liquid crystal and preparation method thereof
CN112708425A
Porphyrinyl covalent organic framework-based sound-sensitive agent as well as preparation method and application thereof
CN114209833A
Ligand-driven porphyrinyl covalent organic framework material stripping method
CN115417960A
Resin film
CN118488994A
Cited By
Greenhouse asparagus beet armyworm control spraying agent and preparation process thereof
CN120036309A
Janus foam evaporator with double-layer heterostructure and preparation method thereof
CN122705014A